Self-Efficacy and Anxiety among Undergraduate University Students - Yusof, Junaidah; Ng, Wai Meng; Ravindran, Divinesh; James Iruthianatham, Veronica; Phoon , Jia Yi; Lee, Mun Leng; Sow, Farrah (Journal of Social Transformation and Regional Development, 2020)
Most university students upon graduation are likely to pursue further studies or begin their career in a chosen field. Many will think that they have the ability and skills to be a competitive candidate in their respective pathways. Naturally, the level of self-efficacy for each individual differs based on their background and personality. High self-efficacy helps an individual believe that they can excel in their work. However, not all students believe they have the ability to complete their task, which will likely lead to increased anxiety. A study was conducted to explore the directional effect between general and social self-efficacies on anxiety among students of public and private institutions. A total of 120 participants were involved in the study from both public and private institutions in Malaysia. Questionnaires were distributed to collect the data, which was then analyzed using multiple regression. The results revealed that general self-efficacy has a negative significant effect on anxiety whereas social self-efficacy has no significant effect on anxiety. Future studies could be expanded to include a larger sample size as well as include different sample populations. Another possibility is to explore the difference in anxiety levels for high vs. low self-efficacy and public vs. private university students.